"Tone Down a Bit": Multi-Scalar Struggles among Feminist Activists in Post-2010 Kenya. - Kaskinen, Martta (Signs: Journal of Women in Culture & Society)
In light of rising femicide rates and the anti-gender ideological front, Kenyan feminists have recently faced pressure to stand as a uniform movement. Nevertheless, young feminist activists have become increasingly vocal in their criticism of mainstream feminist priorities and tactics, especially matters of LGBTQI inclusion and organizational frameworks. This article builds on recent feminist literature on new modes of activism that are challenging established forms of civil society mobilization, and it analyzes such trends within the context of feminist action in Kenya. Combining postcolonial and transnational feminist frameworks, it seeks to emphasize multi-scalar relations in a context in which feminist activism has historically been framed by the discourse and structures of development. Drawing on young Kenyan feminist activists' experiences, it illustrates the complex and overlapping processes through which activists pursue feminist unity despite their open criticism of the mainstream feminist movement and despite their experiences of violence in mainstream feminist discussions. Based on qualitative research, this article discusses how Kenyan feminist activists negotiate their political agency and feminist positionality under dynamic cross-pressures, and it focuses specifically on material needs and the violent processes of silencing. Through their experiences of inclusion, exclusion, and hopes about unity and recognition, the activists discussed in this article embody dynamic and hybrid feminist positionalities in the cross-pressures of strategic necessity and precarious circumstances.